Lockdown fatigue: A content analysis of how the COVID-19 pandemic was framed in South African newspapers before, during, and after the termination of the National State of Disaster - Solomons, Soligah (Centre for Film and Media Studies, 2024)
Both domestically and abroad, the COVID-19 pandemic has gotten a lot of media attention. When covering crises, the media frequently uses frames. This study looks at the frames used by the media to cover the time leading up to, during, and following the termination of South Africa's national state of disaster. The study examines the media coverage of four weekly print newspapers using content analysis. Additionally, a deductive analytical method is employed to discover the frames beforehand, including the alarming frame, neutral frame, and reassuring frame. The results of this study showed that the media's reporting was predominantly alarmist in nature. The reassuring frame and the neutral frame respectively came next. Males made up the majority of the sources for the reporting, who were mostly representatives of various agencies. The majority of the stories analysed at this time gave no information about the abolition of the national state of disaster. Additionally, the few stories that did cover the pandemic often omitted information on what it meant for citizens after the two-year lockdown regulations were lifted. According to this research, the media's overall coverage of the COVID-19 virus has reduced. This study also shows that despite advancements in the COVID-19 viral control methods put in place, the media continued to portray the situation as alarming. Keywords: media framing, COVID-19/covid-19, coronavirus, newspapers, public health crises, pandemics, South Africa